Las tics como herramienta didáctica en el proceso enseñanza aprendizaje de los estudiantes del sexto y séptimo grado de educación general básica de la unidad educativa “Fernando Suárez Palacio” de la ciudad de Loja, periodo 2013 – 2014. Lineamientos alternativos - Cueva Jara, Graciela Piedad (2014)
This research work includes a major in education-related topic "ICT'S AS A TEACHING TOOL IN THE PROCESS TEACHING LEARNING STUDENTS OF THE SIXTH AND SEVENTH GRADE GENERAL EDUCATION BASIC EDUCATION UNIT" FERNANDO SUAREZ PALACE "THE Loja, PERIOD 2013 -.. 2014 ALTERNATIVE GUIDELINES "The overall objective in the project is to determine the impact of ICT's as a teaching tool in the teachinglearning process of students in sixth and seventh grade general education Basic Unit Educational "Fernando Suarez Palace" from the city of Loja, period 2013-2014. The research process unfolded considering methods: scientific, analytic, synthetic, inductive, deductive, descriptive. The technique used was a survey, for which the respective instruments to be applied to the area of computer teachers and students were designed, these procedures allowed for the theoretical and field research; Additional data tabulation, analysis and interpretation of results, the achievement of objectives and respective conclusions and recommendations. In obtaining the final results of the investigation, it was found that there is little use of the Internet by teachers in the teaching - learning process computer, due to the lack of laboratory equipment and outdated computers; The methodology used by teachers in the teaching-learning process of computing, is appropriate because they use the constructivist approach and active learning techniques such as extracting the main idea, crossword puzzles, brainstorming and demonstrations; also determined that teachers have developed a manual for the use of internet for teaching - learning computing students.